1961
DOI: 10.1017/s0031182000068578
|View full text |Cite
|
Sign up to set email alerts
|

Certain aspects of the host-parasite relationship of Nematospiroides dubius (Baylis). I. Resistance of male and female mice to experimental infections

Abstract: 1. It has been shown that there is a difference between the resistance of male and female mice to infection with Nematospiroides dubius.2. More parasites were harboured, during both the larval and adult parasitic phases, by male mice.3. These worms were found to occupy a similar relative length of the intestine between the stomach and the caecum in male and female mice infected for either 5 or 10 days.4. The relative length of the intestine infected on the fifth day was significantly greater than that infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

1968
1968
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 30 publications
(21 reference statements)
4
35
1
Order By: Relevance
“…Thirdly, there was no significant difference between the sexes in the IgGl response, despite the earlier loss of worms from female BALB/c and NIH mice in these experiments. The greater resistance of female mice to infection is well documented in the literature (Dobson 1961, Dobson & Owen 1978 but, in contrast to our findings, more intense antibody responses have been observed in female relative to male mice by other workers (Dobson & Cayzer 1982, Dobson 1982). Lastly we could not detect any difference in antigen recognition profiles which might have indicated that particular mouse strains limited infection through their ability to identify specific antigens.…”
Section: Discussioncontrasting
confidence: 89%
“…Thirdly, there was no significant difference between the sexes in the IgGl response, despite the earlier loss of worms from female BALB/c and NIH mice in these experiments. The greater resistance of female mice to infection is well documented in the literature (Dobson 1961, Dobson & Owen 1978 but, in contrast to our findings, more intense antibody responses have been observed in female relative to male mice by other workers (Dobson & Cayzer 1982, Dobson 1982). Lastly we could not detect any difference in antigen recognition profiles which might have indicated that particular mouse strains limited infection through their ability to identify specific antigens.…”
Section: Discussioncontrasting
confidence: 89%
“…Similar results also reported by Kennedy and Lie (1974), Wickins and Macfarlane (1971). According to Dobson (1961) females are more susceptible to parasitic infection during breeding season. The parasites were particularly collected from different parts of the alimentary canal and body cavity.…”
Section: Resultssupporting
confidence: 88%
“…We used 40 individually housed virgin female house mice, 10 per treatment group. Because parasite infection with H. polygyrus can differentially affect males and females (Dobson 1961; Dobson & Owen 1978), we used only females. We obtained first generation captive born house mice, whose parents were trapped near Flagstaff, from Dr Lee Drickamer (Northern Arizona University).…”
Section: Methodsmentioning
confidence: 99%